Learning Application Derivative Algebraic Functions: Ethnomathematical Studies and Digital Creator Books - Rani Darmayanti; Baiduri Baiduri; Rahmad Sugianto (Mathematics Education Study Program, 2022)
Learning mathematics has been meaningful if it is associated with real-life problems. Ethnomathematics is an activity in which mathematical concepts are related to the local